1993
DOI: 10.1051/forest:19930505
|View full text |Cite
|
Sign up to set email alerts
|

Représentativité locale des placettes d'inventaire en vue de l'estimation de variables dendrométriques de peuplement

Abstract: (underestimated). When the stands are older and when the simulated plots are larger (0.05-0.10 ha), our results suggest that the larger plot size and the regularization of the structure of the stand induced by silvicultural practices diminish both the variance and the bias of the random error. These results indicate that before using a growth model in order to project regional inventory data it is necessary to check the compatibility between the data used to build the model and the data gathered in an operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
1
7
0
2
Order By: Relevance
“…Three explanations are possible for this discrepancy: (i) sampling errors: the original height growth model had been built on the basis of the stem analysis of dominant trees. In contrast, the dominant height was estimated by NFI on small sample plots, which might result in a similar underestimation problem [35] yet described for c 0 [40]. However, this bias, if any, is likely to be small; (ii) measurement errors: NFI measures height increments on standing trees by counting whorls and shoots and measuring (from the ground) the length of the shoots: this method is not very precise for tall trees, and an overestimation is possible.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Three explanations are possible for this discrepancy: (i) sampling errors: the original height growth model had been built on the basis of the stem analysis of dominant trees. In contrast, the dominant height was estimated by NFI on small sample plots, which might result in a similar underestimation problem [35] yet described for c 0 [40]. However, this bias, if any, is likely to be small; (ii) measurement errors: NFI measures height increments on standing trees by counting whorls and shoots and measuring (from the ground) the length of the shoots: this method is not very precise for tall trees, and an overestimation is possible.…”
Section: Discussionmentioning
confidence: 83%
“…Since Salas et al [40] had demonstrated that NFI sampling scheme resulted in biased estimates of c 0 (underestimation due to plot size), N and G (for young stands only because of census threshold), that these biases could be corrected, the variables N, G and c 0 were corrected before testing the original model of the basal area increment of dominant trees (Eq. (2-2.2)).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations